2019
DOI: 10.1101/698548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Single Neurons to Behavior in the JellyfishAurelia aurita

Abstract: 8Jellyfish nerve nets provide insight into the origins of nervous systems, as both their taxonomic 9 position and their evolutionary age imply that jellyfish resemble some of the earliest 10 neuron-bearing, actively-swimming animals. Here we develop the first neuronal network model for 11 the nerve nets of jellyfish. Specifically, we focus on the moon jelly Aurelia aurita and the control of 12 its energy-efficient swimming motion. The proposed single neuron model disentangles the 13 contributions of different … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Even with the relatively simple nature of this distributed control mechanism, jellyfish manage to perform complicated maneuvers (21,27). Ultimately, the turn was initiated by a temporal mismatch in the contraction of opposite sides of the bell by controlling propagation of muscle contraction around bell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the relatively simple nature of this distributed control mechanism, jellyfish manage to perform complicated maneuvers (21,27). Ultimately, the turn was initiated by a temporal mismatch in the contraction of opposite sides of the bell by controlling propagation of muscle contraction around bell.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting wave of muscular activation travels along the bell margin, yielding an asymmetrical contraction. Recent studies have incorporated network neural models to demonstrate the passage of action potentials in the MNN (27).…”
mentioning
confidence: 99%
“…Models of hydrostatic skeletons are rare and have focused on muscular hydrostats, including leech (Wadepuhl and Beyn, 1989; Skierczynski et al, 1996) and octopus tentacles (Yekutieli et al, 2005) . Related work has explored the neural control of swimming in jellyfish (Pallasdies et al, 2019) ; in this case the animal is an open membrane and the model treats the hydrodynamic interaction with the surrounding fluid. We constructed our model using the COMSOL Multiphysics ® 5.3 package.…”
Section: Methodsmentioning
confidence: 99%
“…While there have been exciting developments of predictive models that incorporate musculoskeletal dy-namics in humans and an array of vertebrate and invertebrate animals (Daniel, 1995; Rajagopal et al, 2016; Delp and Loan, 2000; Ting and Chiel, 2017) , many are hampered by the inability to observe the system in its entirety, with simultaneous spatial and temporal patterns of neural activity, muscular activation and whole animal behavior. Small model systems pose the opportunity to develop relatively complete models of the transformations from neural activity to behavior, taking into account the biomechanics of the body (Kim et al, 2019; Pallasdies et al, 2019; Kim and Shlizer-man, 2020) . As an active medium, however, muscle tissue has its own dynamics that can contribute significantly to this transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individual Sarsia are known to each use a unique set of contraction frequencies while swimming [62]. Katija et al 2015 [8] found that Sarsia tubulosa tend to swim about 2 bodylengths per contraction, with a range between [1,3.5] [56,57,[64][65][66][67][68][69][70][71][72] and have compared swimming performance over a large mechanospace, including bell stiffness and flexibility, muscular contraction strength and amplitude, and contraction frequencies. While many in situ and laboratory studies have been performed that quantify bell kinematics, velocity, acceleration, feeding (predation), and/or vortex wake structure [8,46,54,55,58,63,[73][74][75][76][77][78][79][80][81][82], computational studies are becoming increasingly more of an attractive alternative and/or complement for scientists, as they is easier (e.g., more cost and time efficient) to do widespread parameter studies.…”
Section: Introductionmentioning
confidence: 99%